Geochemical fingerprints of brannerite (UTi2O6): an integrated study. (3rd April 2020) - Turuani, Marion; Choulet, Flavien; Eglinger, Aurélien; Goncalves, Philippe; Machault, Julie; Mercadier, Julien; Seydoux-Guillaume, Anne-Magali; Reynaud, Stephanie; Baron, Fabien; Beaufort, Daniel; Batonneau, Yann; Gouy, Sophie; et al.
Abstract: Brannerite (UTi2 O6 ) is among the major uranium-bearing minerals found in ore deposits, however as it has been long considered as a refractory mineral for leaching it is currently disregarded in ore deposits. Brannerite is found in a variety of geological environments with the most common occurrences being hydrothermal and pegmatitic. On the basis of scanning electron microscopy observations coupled with electron probe micro-analyses and laser ablation inductively-coupled plasma mass spectrometer analyses, this study describes the morphological features and the major- and trace-element abundances of brannerite samples from five hydrothermal and five pegmatitic localities across the world. Mineral compositions are also compared with observations from transmission electron microscopy and Raman spectrometry showing that brannerite is amorphous. Significant results include the definition of substitution trends and REE patterns, which are characteristics of either an occurrence or genetic type (hydrothermal and pegmatitic). Hence, in combination, it is possible to obtain reliable constraints for establishing a geochemical classification of brannerite. Inferred fingerprints have direct implications for forensic science and the exploration industry; they also contribute to a better understanding of metallogenic processes and to optimising the extraction of uranium.